Standar Isi, Bahasa, dan Penyajian Buku Tematik Terbitan Mediatama Tema 6 Cita-Citaku Seri HOTS - Moh. Afriansyah; Sudirman; Muhammad Tahir (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2022)
Textbooks are one of the most important teaching materials and are widely used in teaching and learning activities. The selection of textbooks should pay attention to aspects of the feasibility and quality of books so that textbooks can be used optimally in learning. Currently, many publishers and textbook authors are publishing the HOTS series of books. From the many publishers and authors of the book, it is possible to create different presentations of books. Therefore, it is possible that the books in circulation have not met the predetermined eligibility standards. This of course can be a source of problems in the learning process. This study aims to determine the conformity of content standards, language, and presentation of thematic books published by Mediatama theme 6 Cita-Citaku HOTS Curriculum 2013 with the standards set by BSNP. The approach used in this research is qualitative research with the type of content analysis research (content analysis). Methods of data collection using a documentary study. Data analysis using data analysis according to Krippendorff. The results showed that the conformity of content standards, language and presentation of thematic books published by Mediatama theme 6 Cita-Citaku HOTS Curriculum 2013 was obtained: (1) conformity to content standards was 93.06% or very appropriate category, (2) conformity to standards language is 88.9% or the category is very appropriate, (3) conformity to the presentation standard is 91.7% or the category is very appropriate